Ex utero intrapartum treatment for giant congenital omphalocele - Chen, Xu-Yong; Yang, Ji-Xin; Zhang, Hong-Yi; Xiong, Xiao-Feng; Abdullahi, Khalid Mohamoud; Wu, Xiao-Juan; Feng, Jie-Xiong (World journal of pediatrics : WJP, 2018)
Background To determine whether ex utero intrapartum treatment (EXIT) is an appropriate approach for managing fetuses antenatally diagnosed with giant congenital omphaloceles. Methods We retrospectively reviewed patients with omphaloceles who underwent either an EXIT procedure or a traditional repair surgery. Basic and clinical parameters including gender, gestational age, birth weight, maternal blood loss, operative times and operative complications were analyzed. During the 6–12-month follow-ups, postoperative complications including bowel obstruction, abdominal infections, postoperative abdominal distension were monitored, and survival rate was analyzed. Results A total of seven patients underwent the EXIT procedure and 11 patients underwent the traditional postnatal surgery. We found no differences in maternal age, gestational age at diagnosis, gestational age at delivery and birth weight between the two groups. In the EXIT group, the average operation time for mother was 68.3 ± 17.5 minutes and the average maternal blood loss was 233.0 ± 57.7 mL. The operation time in the EXIT group (22.0 ± 4.5 minutes) was shorter than that in the traditional group (35 ± 8.7 minutes), but the length of hospital stay in the EXIT group (20.5 ± 3.1 days) was longer than that in the traditional group (15.7 ± 2.5 days, P < 0.05). During the follow-up, one patient in the EXIT group had an intestinal obstruction, one developed abdominal compartment syndrome and one died in the traditional group. Conclusions In our experience, EXIT is a safe and effective procedure for the treatment of giant congenital omphaloceles. However, more experience is needed before this procedure can be widely recommended.